Transverse Testicular Ectopia: A Rare Case Report (Faridpur Medical College Journal, 2021)
Transverse testicular ectopia (TTE) is a rare but well-known congenital anomaly that occurs 1 in 4 million in which both testes migrate toward the same hemiscrotum. In most of the cases it is an intra-operative finding, but preoperative diagnosis can be made by careful history taking, physical examination and imaging studies. Further evaluation is very important because it can be associated with other congenital anomalies. We report a case of TTE in a 32 years old male who presented with sudden painful swelling in right inguinoscrotal region. Physical examination revealed right sided obstructed inguinal hernia and left sided non palpable testis with underdevelopment of left hemiscrotum. On exploration, one testis is found within the hernial sac and the other testis within scrotum of same side. The testis which was already in right side of scrotum was kept in same place and the other testis which was found within hernial sac was kept in subdartos pouch at the root of right side of scrotum.Faridpur Med. Coll. J. 2021;16(1):52-54